Trajectory generation for a remotely operated vehicle - Sérgio Loureiro Fraga (2003)
This paper addresses the problem of trajectory generation for a remotely operated vehicle (ROV). The ROV is a nonholonomic vehicle and has limited actuator capabilities. This means that the task of trajectory generation for the inspection of underwater structures is not a trivial one, and that it cannot be done without computer aided design tools. The approach is based on techniques developed for differential flat systems. The ROV model is presented and it is shown that it satisfies the differential flatness property. The paper details the architecture of the computer aided trajectory generation tool. Â(c) 2003 EUCA.